Starting with x=1, subtract 1 from each side,
(x-1)=0
Our polynomial will have multiplicity of 2 for this particular zero,
(x-1)(x-1)
and do similar with the x=-4, add 4 to each side,
(x+4)=0
So our final result is: (x-1)(x-1)(x+4)
Expand out the brackets if you need this in standard form.
Since both are equivalent to y, the equations must be equivalent.
x^2-x-3= -3x+5
x^2+2x-8=0
(x+4)(x-2)=0
x=-4, x=2
Plug the values of x in to either equation
y=-3(-4)+5
y= 12+5
y=17
y= -3(2)+5
y=-6+5
y=-1
Final answer: (-4,17) and (2,-1)
I hope this helps you
x+11=5x-5
4x=16
x=4
Answer:
B and D
Step-by-step explanation:
The quadratic formula is
. Here a=20, b=-26, and c=8.
Substitute and you'll have:
This means the solutions are 26 - 6/ 40 and 26 + 6/ 40.
It simplifies to 1/2 and 4/5.